Novel clinical presentation and PAX6 mutation in families with congenital aniridia - Guo, Ruru; Zhang, Xiaotian; Liu, Aihua; Ji, Jian; Liu, Wei (Frontiers in Medicine, 2022)
Purpose: To explore the clinical phenotype and genetic defects of families with congenital aniridia. Methods: Four Chinese families with aniridia were enrolled in this study. The detailed ocular presentations of the patients were recorded. Whole exome sequencing (BGI MGIEasy V4 chip) was used to detect the gene mutation. Sanger sequencing was performed to validate the potential pathogenic variants, and segregation analysis was performed on all available family members. Results: By whole exome sequencing and Sanger sequencing, three recurrent mutations (c.299G>A, p.Trp100*; c.112del, p.Arg38Glyfs*16 and c.718C>T, p.Arg240*) and one novel mutation (c.278_281del, p.Glu93Alafs*30) of PAX6 were identified. All the mutations were co-segregated with the phenotype in the families. We also observed spontaneous anterior lens capsule rupture in aniridia for the first time. Conclusion: We report spontaneous anterior lens capsule rupture as a novel phenotype of aniridia and three recurrent mutations and one novel mutation of PAX6 in families with aniridia. Our results expanded the phenotype and genotype spectra of aniridia and can help us better understand the disease.